1993
DOI: 10.4141/cjas93-094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding organic acids on gastrointestinal digesta measurements at various times postweaning in pigs challenged with enterotoxigenic Escherichia coli

Abstract: . 1993. Effect of feeding organic acids on gastrointestinal digesta measurements at various times postweaning inpigschallengedwithenterotoxigenicEscherichincoli.Can. J. Anim. Sci.73: 931-940.InStudy 1, pigs (n : 54) weaned at2l -l 2 dwere fed. a20% CP corn-soybean meal based diet only (control) or with l.5 % fumaric or 15% citric acid. One half of the pigs on each treatment were orally challenged on days 3,7 or 14 postweaning with 1010 E. coli (0157:K88+) to observe the effects on scouring and on intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
3
19
1
1
Order By: Relevance
“…No differences (P>0.05) were observed on diarrhea incidence among animals (Table III). Similar results reported by Risley et al (1993) and Braz et al (2011) found no differences on diarrhea occurrence when diets were evaluated with combinations of organic acids for piglets. The fact that animals had been housed in pens subjected to a long empty period before the beginning of the experiment, although not desinfected, have contributed to a low health challenge what might explain the ineffectiveness of acidifier blend or fumaric acid on diarrhea reduction in piglets kept on that health challenge status.…”
Section: Methodssupporting
confidence: 87%
“…No differences (P>0.05) were observed on diarrhea incidence among animals (Table III). Similar results reported by Risley et al (1993) and Braz et al (2011) found no differences on diarrhea occurrence when diets were evaluated with combinations of organic acids for piglets. The fact that animals had been housed in pens subjected to a long empty period before the beginning of the experiment, although not desinfected, have contributed to a low health challenge what might explain the ineffectiveness of acidifier blend or fumaric acid on diarrhea reduction in piglets kept on that health challenge status.…”
Section: Methodssupporting
confidence: 87%
“…This action is explained by a reduction of total E. coli persistence. In contrast to our data, the absence of improvement in the experiments by Risley et al (1993) can be explained by the different organic acids or by the dose of supplementation. Our data concerning the use of fat-protected formate are not conclusive.…”
contrasting
confidence: 99%
“…An improvement of growth after weaning has been averagely demonstrated with a meta-analysis of feeding trials (Partanen and Mroz, 1999). However data showing that organic acids can positively counteract the presence of post-weaning diarrhoea and of enterotoxigenic E. coli k88 (ETEC) (Tsiloyiannis et al, 2001) contrast with the absence of positive results in ETEC challenged pigs (Risley et al, 1993). It cannot be excluded that differences in the response to acidifiers can depend on individual susceptibility to ETEC.…”
mentioning
confidence: 99%
“…Η προσθήκη αυ τή προκάλεσε, επίσης, μείωση του πληθυσμοΰ E. coli στη νήστιδα, αλλά όχι και στα άλλα μέρη του γαστρε ντερικοΰ σωλήνα. Σε άλλους όμως πειραματισμούς, η προσθήκη 15 g κιτρικοΰ ή φουμαρικοΰ οξέος /kg τρο φής δεν είχε ουσιαστική επίδραση στον πληθυσμό των γαλακτοβακιλλων, των κλωστηριδιων και της E. coli στο στόμαχο, τη νήστιδα, τον ειλεό ή το κόλον των χοι ριδίων (Risley et al 1993). Σε μια πρόσφατη in vitro με λέτη (Knarreborg et al 2002) διαπιστώθηκε ότι τα κο-λοβακτηριοειδή εξοντώνονται παρουσία οργανικών οξέων (μυρμηκικό, προπιονικό, βουτυρικό, γαλακτι κό, βενζοϊκό και φουμαρικό οξΰ) στο χαμηλός//του στομάχου, ενώ επηρεάζεται αρνητικά η ανάπτυξη τους οερΗ 5 και 7.…”
Section: μηχανισμος δρασης των οργανικων οξεωνunclassified